The evolutionary paradox of tooth wear: simply destruction or inevitable adaptation? - Stefano Benazzi (Public Library of Science (PLoS), 2013)
Over the last century, humans from industrialized societies have witnessed a radical increase in some dental diseases. A severe problem concerns the loss of dental materials (enamel and dentine) at the buccal cervical region of the tooth. This "modern-day" pathology, called non-carious cervical lesions (NCCLs), is ubiquitous and worldwide spread, but is very sporadic in modern humans from pre-industrialized societies. Scholars believe that several factors are involved, but the real dynamics behind this pathology are far from being understood. Here we use an engineering approach, finite element analysis (FEA), to suggest that the lack of dental wear, characteristic of industrialized societies, might be a major factor leading to NCCLs. Occlusal loads were applied to high resolution finite element models of lower second premolars (P2) to demonstrate that slightly worn P2s envisage high tensile stresses in the buccal cervical region, but when worn down artificially in the laboratory the pattern of stress distribution changes and the tensile stresses decrease, matching the results obtained in naturally worn P2s. In the modern industrialized world, individuals at advanced ages show very moderate dental wear when compared to past societies, and teeth are exposed to high tensile stresses at the buccal cervical region for decades longer. This is the most likely mechanism explaining enamel loss in the cervical region, and may favor the activity of other disruptive processes such as biocorrosion. Because of the lack of dental abrasion, our masticatory apparatus faces new challenges that can only be understood in an evolutionary perspective.